The African Union and the challenges it faces: The African Union and the challenges it faces (jornal of the libyan geographical society, 2011)
The African continent witnessed major transformations with the establishment of the African Union. The initial signs of the call for it began at the Algiers Summit on July 12, 1999, where African leaders agreed to accept the invitation from Libya to host the extraordinary summit of the Organization of African Unity in Sirte on September 9, 1999, to discuss ways and means of activating the organization in line with current global conditions and challenges.This extraordinary summit issued what is known as the Sirte Declaration 1, which stipulated for the first time the establishment of the African Union in accordance with the objectives of the Charter of the Organization of African Unity and the provisions of the Abuja Treaty establishing the Economic Community. The General Secretariat prepared the draft Constitutive Act of the Union and presented the draft at the Lomé Summit in Togo, where the Act was officially adopted on 11/7/2000.  After it was signed by 27 countries, Libya called for an extraordinary summit to follow up on the discussion on the subject, which took place in Sirte on March 1-2, and the establishment of the African Union was officially announced.
Keywords: African continent; African Union; Sirte Declaration; Charter of the Organization of African Unity; Constitutive Act of the African Union